Teach yourself visually photoshop elemets 9 - Wooldridge, Mike (Teach yourself visually, 2011)
Explains how to use Photoshop Elements 9, covering topics including working with toolboxes and palettes, mapping photographs, creating slide shows, enhancing contrast and colors, and combining images